Functional characterization of retromer in GLUT4 storage vesicle formation and adipocyte differentiation. Issue 3 (18th November 2015) - Yang, Zhe; Hong, Lee Kian; Follett, Jordan; Wabitsch, Martin; Hamilton, Nicholas A.; Collins, Brett M.; Bugarcic, Andrea; Teasdale, Rohan D.
Abstract : Insulin‐stimulated translocation of glucose transporter 4 (GLUT4) storage vesicles (GSVs), the specialized intracellular compartments within mature adipocytes, to the plasma membrane (PM) is a fundamental cellular process for maintaining glucose homeostasis. Using 2 independent adipocyte cell line models, human primary Simpson‐Golabi‐Behmel syndrome and mouse 3T3‐L1 fibroblast cell lines, we demonstrate that the endosome‐associated protein‐sorting complex retromer colocalizes with GLUT4 on the GSVs by confocal microscopy in mature adipocytes. By use of both confocal microscopy and differential ultracentrifugation techniques, retromer is redistributed to the PM of mature adipocytes upon insulin stimulation. Furthermore, stable knockdown of the retromer subunit‐vacuolar protein‐sorting 35, or the retromer‐associated protein sorting nexin 27, by lentivirus‐delivered small hairpin RNA impaired the adipogenesis process when compared to nonsilence control. The knockdown of retromer decreased peroxisome proliferator activated receptor γ expression during differentiation, generating adipocytes with decreased levels of GSVs, lipid droplet accumulation, and insulin‐stimulated glucose uptake. In conclusion, our study demonstrates a role for retromer in the GSV formation and adipogenesis—Yang, Z., Hong, L. K., Follett, J., Wabitsch, M., Hamilton, N. A., Collins, B. M., Bugarcic, A., Teasdale, R. D., Functional characterization of retromer in GLUT4 storage vesicle formation and adipocyte differentiation. FASEB J. 30, 1037–1050 (2016). www.fasebj.org